MAKNA RELIGIUS ISLAM DALAM SENI UKIR MACAN KURUNG - Suharto Suharto (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2012)
This paper attempts to describe and analyze the sculpture/carving,known as the Macan Kurung (Tiger in a Cage). The data were collectedby the method of documentation, interviews, and observations, while thestudy approach used is semiotics. This article shows that the Tigers Bracketsis a visual language that is full of messages and values. In the contextof Javanese Islam, the tiger is wild creatures as a symbol of wild lust thathave to be caged and chained. Disciplining the passions become an importanttheme of Macan Kurung message. In addition, the Macan Kurungalso a cultural captivity protest message in a colonized society.